Effect of organizational change on sustainable supply chain management: a study of Malaysian SME manufacturers - Kong, Chan Leong; Jaharuddin, Nor Siah; Yee, Choy Leong (Faculty of Arts and Social Sciences, University of Malaya, 2022)
The firm’s change strategy is important to adapt to new changing business environment. As the organizational change is a common phenomenon in a highly competitive business environment with respect to its effect on supply chain management, this study aims to develop an integrative approach on the relationship among organizational change, supply chain disruption, sustainable supply chain management and supply chain resilience. Using data from 324 SME manufacturers, the hierarchical regression analysis shows that there is significant relationship among these variables. Several plausible causal effects are also discussed. In addition, this study offers insight about the impact of organizational change on supply chain management.